2005
DOI: 10.1086/432910
|View full text |Cite
|
Sign up to set email alerts
|

Eruption of a Kink-unstable Filament in NOAA Active Region 10696

Abstract: We present rapid-cadence Transition Region And Coronal Explorer (TRACE) observations which show evidence of a filament eruption from active region NOAA 10696, accompanied by an X2.5 flare, on 2004 November 10. The eruptive filament, which manifests as a fast coronal mass ejection some minutes later, rises as a kinking structure with an apparently exponential growth of height within TRACE's field of view. We compare the characteristics of this filament eruption with MHD numerical simulations of a kink-unstable … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
153
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(163 citation statements)
references
References 19 publications
10
153
0
Order By: Relevance
“…The event on 2004 November 10 (08N 49W) has been reported previously by Williams et al (2005), who observed a highly-localised preflare brightening in TRACE 1600 Å images at 01:52 UT, ∼7 min prior to the flare onset ( Fig. A.2).…”
Section: November 10 (Event 4: On-disk)supporting
confidence: 71%
See 2 more Smart Citations
“…The event on 2004 November 10 (08N 49W) has been reported previously by Williams et al (2005), who observed a highly-localised preflare brightening in TRACE 1600 Å images at 01:52 UT, ∼7 min prior to the flare onset ( Fig. A.2).…”
Section: November 10 (Event 4: On-disk)supporting
confidence: 71%
“…However, at present, we cannot exclude an external tether-cutting (or "breakout") scenario, when precursor HXR brightenings were clearly observed above the loop-top high in the corona (events 5 and 6). One filament eruption (event 4) suggested that internal tether-cutting reconnection may be followed closely by external tether-cutting reconnection, with the magnetic tethers being weakened first at low altitudes, and then later at greater altitudes above the filament (Williams et al 2005). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observations have indicated that newly emerging flux can interact with a pre-existing structure and destabilize it, leading to its dynamical rising motion across the solar atmosphere (e.g. Feynman & Martin 1995;Wang & Sheeley 1999;Williams et al 2005). On the other hand, an AR can create its own "eruptions", aided and incited by the pre-existing coronal magnetic field (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, we do not have sufficient understanding and observational signature of the twisted flux ropes and their evolution from the sub-photospheric level into the corona. There are a few observational signatures related to the generation of the twist in the solar filaments, which causes the disruption of their stable magnetic field configuration and generates solar eruptive events (e.g., Liu and Alexander, 2009;Williams et al, 2005 and references cited there). Rust and LaBonte (2005) have also found evidence of sigmoids in the solar corona which were governed and energized by the magnetic twist, without any large-scale destabilization of magnetic fields and associated eruptions from the Sun.…”
Section: Introductionmentioning
confidence: 99%